Asking better questions of the Bible : a guide for the wounded, wary & longing for more - Solomon, Marty (Theologian) (NavPress, 2023)
"Too often when we come to the Bible, questions make us uncomfortable. But questions are often a good thing. When we stop viewing the Bible through the lens of our own agendas and ask the questions the Bible is asking, something extraordinary happens. We form a new and deeper way of thinking about Scripture and understanding the Bible. As we do, we move further into the depths and mystery of God. Asking Better Questions of the Bible is a journey into the original conversation of the inspired Text. In it, Marty Solomon (a host of The BEMA Podcast and the founder of the BEMA Discipleship ministry, a branch of Impact Campus Ministries) explores all the different portions of Scripture, examining how each is unique in structure and intent. When we ask the questions the Bible is asking, we will: understand the ancient Near Eastern perspective of words, numbers, and core principles like eternal life, truth, sin, and faith; recognize the literary devices and the reclamation of stories used in the Torah; read the historical books both as sources of inspiration and as cautionary tales; interpret the distinct genres in wisdom literature, such as psalms and proverbs; decipher the unique elements of prophetic literature; perceive the subversive nature of the Gospel accounts; and view the New Testament letters as inspired, authoritative interpretation of the story of God. God can be trusted with our doubts and invites us to question. Let Asking Better Questions of the Bible show you a better way forward for interpreting Scripture."--